Effect of Different Movement Speed Modes on Human Action Observation: An EEG Study - Luo, Tian-jian; Lv, Jitu; Chao, Fei; Zhou, Changle (Frontiers in Neuroscience, 2018)
Action observation (AO) generates event-related desynchronisation (ERD) suppressions in the human brain by activating partial regions of the human mirror neuron system (hMNS). The activation of the hMNS response to AO remains controversial for several reasons. Therefore, this study investigated the activation of the hMNS response to a {\color{red}{speed}} factor of AO by controlling the {\color{red}{movement speed}} modes of a humanoid robot's arm movements. Since hMNS activation is reflected by ERD suppressions, electroencephalography (EEG) with BCI analysis methods for ERD suppressions were used as the recording and analysis modalities. Six healthy individuals were asked to participate in experiments comprising five different conditions. Four incremental-{\color{red}{speed}} AO tasks and a motor imagery (MI) task involving imaging of the same movement were presented to the individuals. Occipital and sensorimotor regions were selected for BCI analyses. The experimental results showed that hMNS activation was higher in the occipital region but more robust in the sensorimotor region. Since the attended information impacts the activations of the hMNS during AO, the pattern of hMNS activations first rises and subsequently falls to a stable level during incremental-{\color{red}{speed}} modes of AO. The discipline curves suggested that a moderate {\color{red}{speed}} within a decent inter-stimulus interval (ISI) range produced the highest hMNS activations. {\color{red}{Since a brain computer/machine interface (BCI) builds a path-way between human and computer/mahcine, the discipline curves will help to construct BCIs made by patterns of action observation (AO-BCI).}}Furthermore, a new method for constructing {\color{red}{non-invasive brain machine brain interfaces (BMBIs)}} with moderate AO-BCI and {\color{red}{motor imagery BCI (MI-BCI)}} was inspired by this paper.